(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The whole study was designed to find out probable anti-diabetic potential of various phytoconstituents of Glycyrrhiza glabra and Asparagus racemosus. The study was further aimed at correlating the relationship between various phytoconstituents of both plants with major receptors playing an important role in diabetes mellitus by in silico and in vitro techniques. For in-silico all the constituents were screened by applying ADMET filters. Selected phytoconstituents were further analyzed through molecular docking. Main four PDB’s 1IR3, 1US0, 2FV6, and 20QV for Insulin receptor, Aldose Reductase, Protein tyrosine phosphatase 1 and Human Dipeptidyl Peptidase IV (DPP4), respectively considered in the study. Molegro Virtual Docker version 6.0 tool employed to carry out the whole study. In contrast to internal ligands Licoriphenone, Hyperoside, Quercetin, Licoarylcoumarin, Glyzarin, and Glabrone represent the best docking results with all the four PDB’s. In in vitro alpha-amylase inhibitory assay, both plants’ combination was examined, and results exhibited that 2:1 GAM and 1:2 GAM have higher inhibitory potential than that of individual extract in contrast standard acarbose. The whole study gives insight that both plants probably have anti-diabetic potential due to the presence of studied biomarkers.